Depreciation and Rate Control: A Reply - Young, Allyn A. (Quarterly Journal of Economics, 1915)
Journal Article Depreciation and Rate Control: A Reply Get access Allyn A. Young Allyn A. Young Cornell University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 29, Issue 2, February 1915, Pages 378–387, https://doi.org/10.2307/1884964 Published: 01 February 1915